Um script baseado na biblioteca Scapy que intercepta e bloqueia o tráfego BitTorrent - BRANDÃO, Amós Santos (2019)
Peer-to-peer or P2P applications generate high consumption of internet bandwidth traffic. This work aims to analyze and identify and block the Internet network flow from P2P applications belonging to the BitTorrent protocol. The methodology used is quantitative research based on data collection techniques that are also quantitative. The identification of BitTorrent traffic is done by analyzing the packet payload for BitTorrent protocol characteristics. Some current routers do not offer the option of blocking packets by protocol type of the application layer.